Treatment of severe neuropatic pain for patients with the syndrome of Klippel-Trenaunay-Weber: case report - Soares, Danielle Cristina de Oliveira; de Araújo, José Nilson Fortaleza; Limaverde, Fernando Santiago; Fortaleza, Leila Yasmin Maria Cidrão; Paulino, Grêta Palácio; Oliveira, Lean de Sousa; Oliveira, Lean de Sousa (Journal of Health & Biological Sciences, 2016)
Introduction: Klippel-Trenaunay-Weber syndrome is a rare congenital anomaly whose etiology has not yet been elucidated. It is characterized by the triad of vascular malformations, cutaneous hemangiomas and overgrowth of bone and soft tissue adjacent. Pain is a common symptom and can be triggered in the following situations: venous disease, scoliosis by the different members and hemangiomas that affect the body surface, the deep planes or viscera. Case report: A female patient, 17, sent from the SARAH Hospital - Fortaleza to the Institute of Clinic Pain José Frota diagnosed with cerebral palsy type triplegia on right eye and anophthalmia featuring an expansive process of vascular origin extending to the paraspinal region, surpassing sciatic foramen and affecting posterior muscles of the left thigh and leg. There are signs of involvement of the sciatic nerve and deep femoral vessels. He was diagnosed with Klippel-Trenaunay-Weber syndrome. She had continuous pain in shock and burning, EVA 10, extending from the lower back, groin and left leg region. The source of hospital treatment consisted of gabapentin 180mg 12/12h, codeine 10mg 12/12h, ibuprofen 300mg 12/12h, codeine/paracetamol 30mg 12/12h and morphine oral 10mg while in pain, but without pain relief. She also used paroxetine 20mg daily, due to depression. The painful condition prevented sleep, caused irritation and worsened the quality of life of the patient. She continued treatment with gabapentin 300mg 12/12h, dipyrone 500mg 12/12h, Methadone 5mg 12/12h and reassessed two weeks showing significant improvement in pain symptoms and sleep, EVA 2. Conclusion: Pain is a symptom commonly described in the clinical picture of patients with this syndrome. The treatment of this disease is still a challenge. The malformations great gifts made it not always possible embolization or painkillers locks. The therapeutic results with strong opioid were satisfactory and have improved the quality of life of the patient.